A proposal for a correlation to calculate pressure drop in reticulated porous media with the help of numerical investigation of pressure drop in ideal & randomized reticulated structures. (29th June 2021) - Rambabu, S.; Kartik Sriram, K.; Chamarthy, Siddharth; Parthasarathy, P.; Ratna kishore, V.
Highlights: Investigation to estimate pressure drop in reticulated porous structures. A correlation to calculate pressure drop in porous media is proposed. The proposed correlation is valiadted with data avaliable in literature. Abstract: This paper presents a numerical investigation to estimate pressure drop in fluid flow through reticulated ideal and randomized porous structures. The 3D open-cell foam geometries are constructed using an in-house code along with the use of visualization tool kit (VTK) libraries. In this study, the ideal and randomized Kelvin structures with different porosities and pore densities are generated. These structures have been used to perform direct pore level simulations (DPLS) with the aid of a commercial CFD software. The simulation results are used to acquire the pressure drop across the structures. The pressure drop variation with respect to pore density, porosity, specific surface area, and randomization are analyzed and a pressure drop correlation for reticulated structures with new values of viscous and inertial coefficients is proposed. The validity of the proposed correlation is compared against the experimental and numerical data of the real structures that are available in the literature.